Strong Convergence of a New Hybrid Iterative Scheme for Nonexpensive Mappings and Applications. (19th March 2022) - Jia, Jie; Shabbir, Khurram; Ahmad, Khushdil; Shah, Nehad Ali; Botmart, Thongchai
Abstract : In the article, we have proposed a new type of hybrid iterative scheme which is a hybrid of Picard and Thakur et al. repetitive schemes. This new hybrid iterative scheme converges faster than all leading schemes like Picard-S ∗ hybrid, Picard-S, Picard-Ishikawa hybrid, Picard-Mann hybrid, Thakur et al. and Abbas and Nazir, S-iterative, Ishikawa and Mann iterative schemes for contraction mapping. By using the Picard-Thakur hybrid iterative scheme, we can find the solution of delay differential equations and also prove some convergence results for nonexpansive mapping in a uniformly convex Banach space.